The impact of transformational leadership on improving job performance: A case study in the National Employment Agency in Algeria - Sid Hayet; Mostefaoui Soufiane; llali.zahra (Journal of North African Economies, 2025)
This study aimed to reveal the Impact of transformational leadership in its dimensions (Idealized Influence, individualized consideration, Intellectual Stimulation, and inspirational stimulation) in improving job performance in the National Employment Agency, and to verify the validity of hypotheses. The questionnaire was used as a means of collecting data, and the number of answers reached (226). A questionnaire, and for its analysis, the plspm R 3.5.1 program was used, and the results revealed that there is no significant impact of transformational leadership in its dimensions on job performance in the studied organization. The study recommended raising the level of performance with good supervision, fair treatment, and continuous communication within the organization. Keywords: transformational leadership; Idealized Influence; Inspirational Motivation; Intellectual Stimulation; job performance